On human body transmission wearable diamond dipole antennas above engineered jackets - Muhammad Azfar bin Abdullah; Mohamad Kamal A. Rahim; Noor Asmawati Samsuri; Mohd Fairus; Mohd Khairul Hisham Ismail; Huda A. Majid (Institute of Advanced Engineering and Science, 2021)
This paper presents the propagation of dual-band diamond dipole antenna on three various jackets. The jackets are purely fleece fabric with Shieldit fabric patches on top of it. The network analyzers with the flexible lossless coaxial cable are used to measure the communication of the antennas. The experiment involves a man with ideal body mass index (BMI) wearing the jackets by placing the flexible antennas on top of it. It is observed that the best on-body communication is by wearing the engineered jacket. The 10 dB improvements are observed when the antenna is positioned on top of engineered jacket contrast to the regular jacket. In other words, the performance of the antenna is also be determined by antenna placement. High transmission lossesses cause the antenna mismatch when the antennas are positioned above the full conductive jacket.